2012
DOI: 10.1007/s10753-012-9432-y
|View full text |Cite
|
Sign up to set email alerts
|

A High Molecular Weight Protein Extract of Mastobranchus indicus (Mi-64) Having Antiarthritic Activity in Experimental Animals

Abstract: Mi-64, a high molecular weight protein (130 kDa), obtained from the tissue homogenate of marine polychaete (Mastobranchus indicus) collected from the Indian Sunderban has antiarthritic activity in experimental animals. The FCA-induced arthritis model was developed in Wistar albino rats to evaluate the antiarthritic effects of Mi-64. After FCA induction, the rats were treated with Mi-64 (0.25 and 0.5 mg kg(-1) body weight) for 10 days. We have determined the paw/ankle swellings, urinary hydroxyproline and gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Mi-64, a high molecular weight protein (130 kDa), obtained from marine polychaete (Mastobranchus indicus) collected from the Indian Sunderban significantly inhibited the overproduction of interleukin-1 beta, interleukin-6, chemoattractant-1, and tumor necrosis factor-alpha and augmented interleukin -10 production. The study indicated the role of Mi-64 as potential antiarthritic agent (Alam et al, 2012).…”
Section: Marineactinomycetes Identified As Streptomyces Sparsus Upon Analysis Revealed the Presence Ofmentioning
confidence: 89%
“…Mi-64, a high molecular weight protein (130 kDa), obtained from marine polychaete (Mastobranchus indicus) collected from the Indian Sunderban significantly inhibited the overproduction of interleukin-1 beta, interleukin-6, chemoattractant-1, and tumor necrosis factor-alpha and augmented interleukin -10 production. The study indicated the role of Mi-64 as potential antiarthritic agent (Alam et al, 2012).…”
Section: Marineactinomycetes Identified As Streptomyces Sparsus Upon Analysis Revealed the Presence Ofmentioning
confidence: 89%